2011
DOI: 10.1007/s00404-011-2065-9
|View full text |Cite|
|
Sign up to set email alerts
|

Uterine artery embolization versus surgery for symptomatic uterine fibroids: a randomized controlled trial and a meta-analysis of the literature

Abstract: Compared with surgery, UAE has a shorter hospital stay, a shorter recovery time, and less major complications. More studies in the future need to done to evaluate its long-term effects and impact on fertility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 24 publications
3
35
0
4
Order By: Relevance
“…Em médio e longo prazo, os benefícios foram similares, com exceção de uma taxa de reintervenção maior após a EAU (VAN DER KOOIJ et al, 2011). Confirmando os estudos brasileiros e levando em consideração as diferenças metodológicas e técnicas entre os estudos, em comparação com a cirurgia, as pacientes submetidas à EAU apresentaram menos complicações graves (JUN et al, 2012;MARTIN et al, 2013) e melhora na maioria dos aspectos de qualidade de vida após 6 meses (JUN et al, 2012).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Em médio e longo prazo, os benefícios foram similares, com exceção de uma taxa de reintervenção maior após a EAU (VAN DER KOOIJ et al, 2011). Confirmando os estudos brasileiros e levando em consideração as diferenças metodológicas e técnicas entre os estudos, em comparação com a cirurgia, as pacientes submetidas à EAU apresentaram menos complicações graves (JUN et al, 2012;MARTIN et al, 2013) e melhora na maioria dos aspectos de qualidade de vida após 6 meses (JUN et al, 2012).…”
Section: Resultsunclassified
“…Apesar de não ter sido uma variável pesquisada nos estudos brasileiros, a embolização parece reduzir significativamente o tempo de internação hospitalar e proporcionar um retorno rápido às atividades rotineiras, quando comparada às cirurgias como histerectomia ou miomectomia (GUPTA et al, 2012;JUN et al, 2012;VAN DER KOOIJ et al, 2011). Por outro lado, as chances de uma nova intervenção cirúrgica dentro de cinco anos foram significativamente maiores após a EAU, tornando os custos desse procedimento equivalentes aos da histerectomia (GUPTA et al, 2012).…”
Section: Resultsunclassified
“…Çalışmamızın sonuçları göstermiştir ki, UAE, semptomatik uterin fibroidlerin tedavisinde yüksek başarı, yüksek hasta memnuniyeti ve düşük komplikasyon oranları ile cerrahiye iyi bir alternatif oluşturmaktadır. On üç çalışmanın değerlendirildiği bir meta-analizin sonuçlarına göre, UAE, cerrahi ile karşılaştırıldığında (histerektomi ve myomektomi) hastanede kalış süresi, iyileşme süresi ve major komplikasyonlar açısından anlamlı olarak daha avantajlı bulunmuştur (11) . Hastalarımız hiçbirinde işlem sonrası komplikasyona rastlanmazken, yalnızca 1 hastaya (%2,7), takip sürecinde myom boyutlarında anlamlı küçülme olmaması nedeniyle histerektomi uygulanmıştır.…”
Section: Discussionunclassified
“…There are three randomized trials comparing myomectomy to UFE; one completed by Mara et al, 32,33 the Fibroids of the Uterus: Myomectomy versus Embolization (FUME) trial in the United Kingdom, 34 and the most recent by Jun et al in China. 35 In the study by Mara's group, 121 women with a mean age of 32 and an interest in future fertility were randomly assigned to uterine embolization or myomectomy. The primary focus of the first report was on procedural outcomes and confirmed that recovery was shorter and with a shorter hospital stay than myomectomy.…”
Section: Randomized Trialsmentioning
confidence: 99%